2003
DOI: 10.1097/01.shk.0000087203.34916.45
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Necrosis Factor-?? Therapy During Murine Klebsiella pneumoniae Bacteremia: Increased Mortality in the Absence of Liver Injury

Abstract: Klebsiella pneumoniae is a leading cause of gram-negative bacterial pneumonia, often resulting in bacteremia concurrent with the localized pulmonary infection. The beneficial role of tumor necrosis factor (TNF)-alpha during pulmonary infection has been well documented; however, consequences of TNF-alpha production during systemic bacterial infection are controversial. A murine model of K. pneumoniae was developed to address this important issue. Liver-associated TNF-alpha mRNA was induced within 30 min after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
3
24
0
1
Order By: Relevance
“…These studies indicated that IFN-␥ is a critical mediator for the resolution of localized, pulmonary gram-negative pneumonia, whereas resolution of systemic, blood-borne gram-negative bacterial infections is independent of IFN-␥ secretion (16). In contrast, in our murine model of Klebsiella bacteremia, mice receiving antitumor necrosis factor alpha (anti-TNF-␣) treatment displayed increased mortality that correlated with impaired bacterial clearance (13,15). These studies, however, did not address the cellular source of these cytokines induced during Klebsiella bacteremia.…”
mentioning
confidence: 43%
See 3 more Smart Citations
“…These studies indicated that IFN-␥ is a critical mediator for the resolution of localized, pulmonary gram-negative pneumonia, whereas resolution of systemic, blood-borne gram-negative bacterial infections is independent of IFN-␥ secretion (16). In contrast, in our murine model of Klebsiella bacteremia, mice receiving antitumor necrosis factor alpha (anti-TNF-␣) treatment displayed increased mortality that correlated with impaired bacterial clearance (13,15). These studies, however, did not address the cellular source of these cytokines induced during Klebsiella bacteremia.…”
mentioning
confidence: 43%
“…Survival following infection was then observed over the course of 10 days. As we have previously reported (13,15,16), this dose of K. pneumoniae results in a mortality rate of 50% in wild-type animals, with the majority of death occurring within 2 to 4 days of infection. Interestingly, ␤2-m KO mice were significantly more susceptible to K. pneumoniae infection, with 90% of the infected animals succumbing by day 5 postinfection (Fig.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…K. pneumoniae is an important cause of community-acquired pneumonia in individuals with impaired pulmonary defenses and is a major pathogen in nosocomial pneumonia (19,20). Results obtained using the mouse model of Klebsiella pneumonia highlight the fact that the clearance of the pathogen is primarily dependent upon a vigorous innate immune response (21)(22)(23)(24)(25)(26)(27)(28). Furthermore, stimulation of this response enhances bacterial clearance and prolongs animal survival (29)(30)(31)(32).…”
Section: Drosophila Melanogaster Caenorhabditis Elegans and The Fishmentioning
confidence: 99%